EVALUASI PROGRAM 5S SEBAGAI PENDIDIKAN KARAKTER bagi PESERTA DIDIK di SDN KALICACING 02 SALATIGA - Sri wiji (Jurnal Ilmiah Pendidikan TRISALA, 2022)
Character education needs to be implemented as early as possible, including at grade I. The 5S program (Smile, Greetings, Greetings, Politeness and Courtesy) is one of the efforts to instill character in students. This study aims to describe the implementation of the 5S program at SDN Kalicacing 02 Salatiga. The subjects of this study were homeroom teachers and class I students at SDN Kalicacing 02 Salatiga as many as 12 people. Observations and interviews were used to collect data on the implementation of this 5S program. The results showed that the implementation of the 5S program in the form of socialization and program realization was carried out well and effectively in instilling positive character values ​​in students. This program needs to be continued as one of the character education efforts for students.